2020
DOI: 10.1007/s10343-020-00503-9
|View full text |Cite
|
Sign up to set email alerts
|

Bioefficacy of Some Aqueous Phytoextracts Against Clavibacter Michiganensis Subsp. Michiganensis (Smith), the Cause of Bacterial Canker of Tomato

Abstract: The ability of some medicinal plants was explored to control bacterial canker of tomato caused by Clavibacter michiganensis subsp. michiganensis. The plants tested included Peganum harmala, Allium sativum, Withania somnifera, Melia azedarach, Calotropis procera, Mentha piperita and Nerium oleander. Aqueous extracts of P. harmala and M. piperita proved to be very effective under in vitro conditions against Clavibacter michiganensis subsp. michiganensis. In in vivo studies, the highest dose of dried powder of P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
3
0
2
Order By: Relevance
“…It was concluded that total alkaloid extract of P. harmala could be an alternative to chemical antimicrobial agents in the treatment of these bacterial diseases. Siddique et al [38] also tested the in vitro inhibitory effect of seven plant extracts including P. harmala on bacteria using a paper disc diffusion method and in vivo inhibitory effect using pot experiments. Oxytetracycline treatment was a positive control.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…It was concluded that total alkaloid extract of P. harmala could be an alternative to chemical antimicrobial agents in the treatment of these bacterial diseases. Siddique et al [38] also tested the in vitro inhibitory effect of seven plant extracts including P. harmala on bacteria using a paper disc diffusion method and in vivo inhibitory effect using pot experiments. Oxytetracycline treatment was a positive control.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…En términos de control químico, se utilizan principalmente antibióticos y compuestos cúpricos como oxicloruro, óxido o hidróxido de cobre (de León et al, 2008;Milijašević et al, 2009). También se ha explorado el control biológico (Nandi et al, 2018), el uso de extractos vegetales (Stefanova Nalimova et al, 2005;Siddique et al, 2020) y bacteriocinas (Mirzaee et al, 2021). Sin embargo, todos estos tratamientos tienen una eficacia limitada debido a la alta variación en la agresividad y virulencia del patógeno (Croce et al, 2016;Wassermann et al, 2020) y la falta de disponibilidad de compuestos antibacterianos comerciales adecuados que mitiguen los diferentes tipos de problemas ambientales y toxicológicos.…”
Section: Introductionunclassified
“…Dentro de las investigaciones realizadas Stefanova Nalimova et al, (2005), encontraron extractos metanólicos de plantas que poseen actividad antimicrobiana frente a bacterias fitopatógenas específicamente del género Xanthomonas en condiciones in vitro. Siddique et al (2020) encontraton actividad de fitoextractos acuosos de plantas contra la bacteria Clavibacter. Por lo tanto, el objetivo de este trabajo fue evaluar la actividad antimicrobiana de la fracción de acetato de etilo de Salvia amarissima, obtenida a partir del extracto soluble en acetona (EC-SA) y de dos diterpenoides: amarissinina A (STJ-3) y C (STJ-1), mediante ensayos in vitro y en invernadero, con relación a su efecto contra Clavibacter michiganensis subsp.…”
Section: Introductionunclassified
“…Michiganensis, is the most important one, as it causes 70% yield losses each year. It was first reported in Michigan, USA (Siddique et al, 2020). Various management strategies are used to manage this disease such as use of resistant varieties, chemical and biological control.…”
Section: Introductionmentioning
confidence: 99%